Evaluation of FeMnN alloy bioresorbable flow diverters in the rabbit elastase induced aneurysm model - Oliver, Alexander A.; Bilgin, Cem; Cortese, Jonathan; Bayraktar, Esref A.; Dai, Daying; Ding, Yong Hong; Carlson, Kent D.; Griebel, Adam J.; Schaffer, Jeremy E.; Connon, Mitchell L.; Dragomir-Daescu, Dan; Kadirvel, Ramanathan; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionFlow diverters are specialized stents used to treat intracranial aneurysms. Bioresorbable flow diverters (BRFDs) have been proposed as the next-generation of flow diverter technology. BRFDs aim to occlude and heal the aneurysm before safely dissolving into the body, mitigating complications associated with the permanent presence of conventional flow diverters. We previously prototyped BRFDs using an iron-manganese-nitrogen (FeMnN) alloy and demonstrated their flow diversion functionality, radial strength, bioresorbability, and MRI compatibility in benchtop tests. In the current work, we investigated their aneurysm occlusion efficacy in vivo.MethodsElastase induced aneurysms were created in seven rabbits and BRFDs were deployed over the aneurysms for 3 months. Aneurysm occlusion efficacy and the biological response was assessed via angiography, gross dissection microscopy, and histology.ResultsThe BRFDs failed to occlude the aneurysms in 5/7 rabbits at the 3-month endpoint. The bioresorbable wires appeared to resorb too rapidly and fragment away from the aneurysm neck prior to becoming entirely encased in tissue and completely occluding the aneurysm. In 3/7 rabbits, some FeMnN wires remained over the aneurysm neck that were encased in tissue, partially covering the aneurysm neck. Histological analysis revealed that the wires, when present, were a suitable substrate over which tissue could develop. Therefore, we attribute the poor aneurysm occlusion efficacy to mechanical failure rather than an impaired biological healing response.ConclusionThe FeMnN BRFDs degraded too rapidly to effectively treat the rabbit elastase induced aneurysms. Future work will focus on developing BRFDs out of materials with a delayed resorption rate.